The Impact of Financial Inclusion on Economic Growth in Syria Compared to a Group of Countries in the Middle East and North Africa (Journal of Hama University, 2021)
The research aims to study the effect of financial inclusion on the economic growth of a sample of Middle Eastern and North African countries. Financial inclusion was measured by two indicators, the first is "availability of banking services" index, the second is the "use of banking services" index, while economic growth was measured by GDP per capita (current us$); and controlling variables were introduced, the first is the inflation rate, the second is the political stability variable.To achieve the research objectives; financial inclusion indicators were constructed, by combining the dimensions of the financial services availability index, and the dimensions of the financial services use index, by using the basic components method (PCA). Then apply stationarity tests for the Panel type data. Then, the ARDL Panel model was assessed to measure the impact of financial inclusion indicators “availability of financial services” and “use of financial services” on the economic growth of the research sample countries. The results of the study showed that financial inclusion indicators in Syria are very low at the level of neighboring countries or the countries of the research sample. We mention from them the demographic penetration of ATMs, which did not exceed at its best cases before the start of the war on Syria and the emergence of the consequences of the crisis (7) ATMs per 100,000 adults in the year (2011). In addition, that the war on Syria has negatively affected the indicators of Syrian financial inclusion, and the per capita gross domestic product in US dollars.The results of the study Also showed, that the financial services availability index, the financial services use index, have a positive impact on the economic growth of the study sample. While political stability affects positively financial inclusion.